Specific CD4+ T Cell Responses to Ancestral SARS-CoV-2 in Children Increase With Age and Show Cross-Reactivity to Beta Variant - Paul, Kevin; Sibbertsen, Freya; Weiskopf, Daniela; Lütgehetmann, Marc; Barroso, Madalena; Danecka, Marta K.; Glau, Laura; Hecher, Laura; Hermann, Katharina; Kohl, Aloisa; Oh, Jun; Schulze zur Wiesch, Julian; et al. (Frontiers in Immunology, 2022)
SARS-CoV-2 is still a major burden for global health despite effective vaccines. With the reduction of social distancing measures, infection rates are increasing in children, while data on the pediatric immune response to SARS-CoV-2 infection is still lacking. Although the typical disease course in children has been mild, emerging variants may present new challenges in this age group. Peripheral blood mononuclear cells (PBMC) from 51 convalescent children, 24 seronegative siblings from early 2020, and 51 unexposed controls were stimulated with SARS-CoV-2-derived peptide MegaPools from the ancestral and beta variants. Flow cytometric determination of activation-induced markers and secreted cytokines were used to quantify the CD4+ T cell response. The average time after infection was over 80 days. CD4+ T cell responses were detected in 61% of convalescent children and were markedly reduced in preschool children. Cross-reactive T cells for the SARS-CoV-2 beta variant were identified in 45% of cases after infection with an ancestral SARS-CoV-2 variant. The CD4+ T cell response was accompanied most predominantly by IFN-γ and Granzyme B secretion. An antiviral CD4+ T cell response was present in children after ancestral SARS-CoV-2 infection, which was reduced in the youngest age group. We detected significant cross-reactivity of CD4+ T cell responses to the more recently evolved immune-escaping beta variant. Our findings have epidemiologic relevance for children regarding novel viral variants of concern and vaccination efforts.